Arguably : essays - Hitchens, Christopher (Twelve, 2011)
Essayist Christopher Hitchens ruminates on why Charles Dickens was among the best of writers and the worst of men, the haunting science fiction of J.G. Ballard, the enduring legacies of Thomas Jefferson and George Orwell, the persistent agonies of anti-Semitism and jihad, the enduring relevance of Karl Marx, and how politics justifies itself by culture--and how the latter prompts the former.